HIGHER EDUCATION DURING AND AFTER THE PANDEMIC: PHILOSOPHY OF DIGITAL CHANGE. - AVETISYAN, Pargev; TITARENKO, Larissa; ZASLAVSKAYA, Maria; GALIKYAN, Gagik (Wisdom, 2022)
The authors discuss the problems associated with the accelerated digitalization of higher education during and after the pandemic. Various approaches proposed by specialists dealing with problems of digitalized higher education are analyzed, and the benefits and risks associated with digital change are identified. The theoretical approach includes some famous theories in the philosophy of education constructed first by John Dewey and developed further by contemporary scholars. The empirical basis contains several studies of students, teachers and experts conducted in Armenia and Belarus. The authors present a comparative analysis of the situation in higher education in both countries during the pandemic. The research results show that the online form of learning poses several difficulties and offers advantages over the traditional form of learning. At the same time, the rejection of traditional forms of learning is also related to the problems and unpredictable consequences of the quality of learning. The authors conclude that currently, the most promising form of learning is hybrid. Its implementation demands a special educational environment to embrace the advantages of online and offline forms of education and account for factors influencing the effectiveness of these forms.